Learning Innovation in Dayah: The Effectiveness of Experiential Learning Methods in Developing Students’ Skills - Anshari, Ismail; Mujiburrahman, Mujiburrahman; Rijal, Fakhrul; Alfadhil, Musa; Tihalimah, Tihalimah (SCAD Independent, 2025)
This study explores the effectiveness of experiential learning in developing students’ competencies within two Acehnese salafiyah dayah: Mudi Mesra and Ummul Ayman. It aims to reinterpret how experiential learning operates across ritual, vocational, institutional, and digital dimensions, thereby formulating a contextual framework for transformative Islamic education. Using a qualitative multiple-case design, data were collected from fifteen participants—including leaders, teachers, and students—through interviews, participatory observation, and document analysis. Thematic analysis, supported by triangulation, member checking, and peer debriefing, ensured credibility and reflexivity. Findings reveal that experiential learning is systematically embedded in ritual and communal practices (muhadzarah, khutbah, tajhiz mayat), vocational and entrepreneurial training (banking, printing, tailoring, IT), institutional mediation through teungku-centered authority, and emerging digital engagement such as WhatsApp-based muzakarah. These practices affirm Dewey’s and Kolb’s experiential frameworks while contextualizing constructivist learning within Islamic communal culture. The study introduces the concept of an “experiential ecology of Acehnese dayah,” which integrates spirituality, institutional authority, and innovation. Theoretically, it enriches global debates on experiential pedagogy in faith-based education; practically, it provides a model for enhancing vocational and digital readiness without compromising religious authenticity.